Pseudoscience in biological psychiatry blaming the body - Ross, Colin A.; Pam, Alvin (Wiley, 1995)
Lately, it seems that not a day passes without the media proclaiming yet another sensational breakthrough in the search for the physical origins of mental illness. But beyond all the fanfare and media hype, is there a single shred of hard, empirical evidence to substantiate the existence of "a gene for alcoholism," or "the brain chemistry behind schizophrenia"? More to the point, in fact, is it scientifically sound to limit the search for the roots of mental illness to processes occurring within the body, while dismissing socioeconomic, familial, and experiential influences as, at best, mere "triggering mechanisms"? And, if not, what harm is being done by psychiatry's current obsession with these somatic chimeras? This groundbreaking book offers answers to those questions and more. While Dr